Land preparation for lowland irrigated rice production in West Africa - Oke, Adebayo; Atengdem, P. B.; Zemadim, Birhanu; Cofie, Olufunke O. (International Water Management Institute, 2025)
Land preparation for irrigated rice cultivation is crucial for optimal yield. It involves a series of steps designed to create a suitable environment for planting and growth. Key activities include leveling the field to ensure even water distribution, which is vital for nutrient uptake and weed control. Tilling, either through plowing and harrowing or puddling, breaks down soil clods and incorporates organic matter. This process also helps manage weeds by burying them and creating a soft soil bed for seedling establishment. Finally, constructing bunds (small earthen ridges) helps to retain water within the field, further aiding weed control and water management. This Fact Sheet highlights the process of land preparation in a lowland irrigated rice system.